Assessment of serum macrophage migration inhibitory factor (MIF), adiponectin, and other adipokines as potential markers of proteinuria and renal dysfunction in lupus nephritis: a cross-sectional study - Jorge Ivan Gamez-Nava; Valeria Diaz-Rizo; Edsaul Emilio Perez-Guerrero; Jose Francisco Muñoz-Valle; Ana Miriam Saldaña-Cruz; Nicte Selene Fajardo-Robledo; Heriberto Jacobo-Cuevas; Cesar Arturo Nava-Valdivia; Miriam Fabiola Alcaraz-Lopez; Xochitl Trujillo; Miguel Huerta; Ernesto German Cardona-Muñoz; et al. (BMC, 2020)
Abstract Background To date, the association of serum macrophage migration inhibitory factor (MIF) and serum adipokines with lupus nephritis is controversial. Objective To assess the utility of serum MIF, leptin, adiponectin and resistin levels as markers of proteinuria and renal dysfunction in lupus nephritis. Methods Cross-sectional study including 196 systemic lupus erythematosus (SLE) patients and 52 healthy controls (HCs). Disease activity was assessed by Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Renal SLE involvement was investigated by renal-SLEDAI. MIF, adiponectin, leptin and resistin levels were quantified by ELISA. We assessed the correlations of quantitative variables by Spearman correlation (rs). Multivariable linear regression adjusted the variables associated with the severity of proteinuria. Results SLE patients had higher MIF (p = 0.02) and adiponectin (p < 0.001) than HCs. Patients with renal SLE involvement (n = 43) had higher adiponectin (19.0 vs 13.3 μg/mL, p = 0.002) and resistin (10.7 vs 8.9 ng/mL, p = 0.01) than patients with non-renal SLE (n = 153). Proteinuria correlated with high adiponectin (r s  = 0.19, p < 0.009) and resistin (r s  = 0.26, p < 0.001). MIF (r s  = 0.27, p = 0.04). Resistin correlated with increased creatinine (r s  = 0.18, p = 0.02). High renal-SLEDAI correlated with adiponectin (r s  = 0.21, p = 0.004). Multiple linear regression showed that elevated adiponectin (p = 0.02), younger age (p = 0.04) and low MIF (p = 0.02) were associated with the severity of proteinuria. Low MIF and high adiponectin levels interacted to explain the association with the severity of proteinuria (R2 = 0.41). Conclusions High adiponectin combined with low MIF concentrations int+eract to explain the severity of proteinuria in renal SLE. These findings highlight the relevance of adiponectin, resistin and MIF as markers of LN.